Management of Giant Cell Tumour by Curettage and Bone Cement in Weight Bearing Bone - A Study Done in DMCH & NITOR. - Karmakar, Narayan Chandra; Uddin, Md Maiyeen; Rahman, Md Masudur; Mondal, Anadi Ranjan; Alam, Syed Asif Ul (Faridpur Medical College Journal, 2017)
Giant cell tumour of bone (GCT) has been characterized as benign but often locally aggressive neoplasm that commonly occurs in proximity to weight bearing bone. Management of giant cell tumor of bone by curettage and bone cement in weight bearing bone is an effective method. This prospective experimental study was conducted among the patients with histologically proved giant-cell tumour who were admitted in the Department of orthopedic surgery, Dhaka Medical College Hospital (DMCH) and in National Institute of Traumatology and Orthopaedic Rehabilitation (NITOR) over a period of 18 months from January 2010 to June 2011. A total of 18 consecutive patients with histologically proved giant-cell tumour were included in the study. Majority (55.6%) of patient was in 3rd decade and male female ratio was 1:1.3. More than one fourth (27.8%) of the patients had GCT in the lower end of right femur, 33.3% in lower end of left femur, 22.2% in upper end of right tibia, 16.7% in upper end of left tibia and all patients had painful gait and swelling. According to campanacci grading, Grade-2 was found in all patients, and giant cell tumour was found in all patients, as evaluated by pre-operative biopsy. Cosmetically near normal appearance was found in 88.9% and 88.9% were able to do normal daily work. According to Schatzker and Lambert (1979) criteria excellent outcome was found in 38.9%, good in 44.4%, fair in 11.1% and poor in 5.6%. Surgery in the form of intralesional curettage and filling the cavity with bone cement resulted in excellent relief of pain, cosmetically near normal appearance and patients were able to do normal daily work. Faridpur Med. Coll. J. Jan 2017;12(1): 9-13